Dan Tompkins: mountain editor - Austin, Suelle Reece (1966)
Rural, isolated Jackson County, North Carolina, was the home of Dan Tompkins, editor of the Jackson County Journal of Sylva. Jackson County rests in North Carolina’s Appalachian Ranges. In the early twentieth century her inhabitants were restricted because of the dearth of transportation and communication facilities.Many of the limitations on Jackson County folks were removed through the efforts of Dan Tompkins. For thirty-one years Tompkins published an honest paper on the reading level of the citizens of Jackson County. Tompkins was a progressive and active leader of his area. Through the Journals’ editorial column and as representative in the General Assembly of North Carolina, he sought to break down the isolation and bring progress to Western North Carolina and Jackson County.Tomkins dreamed of making Western North Carolina the “Switzerland of America.” His dream could be realized, he felt, if the area had paved roads, tourist accommodations, a national park in the Smokies, better public facilities, and a better education for the mountain people.Tompkins was not just a dreamer, he was a man of action. Therefore, many of Tompkins’ dreams were to become realities for Jackson County and Western North Carolina. Dan Tomkins was largely responsible for the paving of Highway 107 from Sylva to the South Carolina line. Because of his heated editorials and active support in the state legislative, Tompkins was an important force in preventing removal of Western Carolina Teacher’s College from Cullowhee to Asheville. Tompkins was also instrumental in getting the state to appropriate money for expanding the facilities of the college.To make realities of his dreams, Dan Tompkins sacrificed any financial success that might have been his. His determination to represent ably the people who elected him to public office was one cause of the folding of the Journal. Tompkins was a most generous individual: he never had very much with which to assist his needy friends materially, but he did possess what was perhaps most needed—a smile and encouragement.Tompkins was an asset to Jackson County. His energies were given unselfishly to the benefit of progress for Western North Carolina. Jackson County and the area owe much to the powerful pen and influence of Dan Tompkins.